Causal relationship between bitcoin price volatility and trading volume: Rolling window approach - Nebiye Yamak; Rahmi Yamak; Serkan Samut (Financial Studies, 2019)
This study investigates the causal relationship between price volatility and trading volume for bitcoin which is the first cryptocurrency. Data are daily and cover the period starting from December 27, 2013 to March 3, 2019. Price volatility series was produced by using EGARCH model. The Toda-Yamamoto causality test was applied under rolling window approach. According to the Granger causality test, there is a strong causal relationship running from the trading volume to the price volatility. There also exists a causality running from price volatility to volume. But this causality isnot statistically strong. At the same time, a positive and significant contemporaneous correlation was found between the two variables. Both findings support the sequential information arrival hypothesis for the bitcoin market.
Keywords: C22; G14; 330; sequential information arrival hypothesis; Toda-Yamamoto causality; cryptocurrency